PRELIMINARY IMPACTS OF THE COVID-19 PANDEMIC ON AGRI-FOOD TRADE: CHALLENGES AND DEVELOPMENT SCENARIOS (CASE OF GEORGIA) (Globalization and Business, 2023)
The role of agri-food trade in food security and agricultural development is substantiated in the article. There are Assessed food trade challenges, export restrictions, and import facilitation during the COVID-19 crisis. The paper examines the changes in supply caused by various factors in the production sector in the agri-food sector, hypothesizing that food demand is relatively stable financially, as well as during various crises.The paper analyzes the views of scientists on the difficulties caused by the pandemic, on the basis of which two development scenarios are formulated. Opportunities have been identified for the continuation of trade in agri-food products between countries, and there is a reasonable view of the incentives for trade in these products in the short and long term.  In the process of research, through comparative analysis, the indicators of trade in agri-food products of Georgia in the pre-pandemic (2018-2019) and post-pandemic (2020-2021) periods are grouped, and positive and negative trade trends are identified. At the same time, based on the results of the global financial crisis and the pandemic, an in-depth analysis of typical and atypical crises has been conducted for the agri-food sector around the world and in Georgia.Based on the results of the research, a matrix has been compiled to determine the growth and decline rates of trade in agri-food products before and during the pandemic.  The paper draws conclusions and makes recommendations on food trade challenges and trade improvement measures during the COVID-19 crisis.